Prevalence of parental alienation drawn from a representative poll. (July 2016) - Harman, Jennifer J.; Leder-Elder, Sadie; Biringen, Zeynep
Abstract: The current work is the first known representative poll of adults ( N  = 610) aimed at determining the prevalence of parental alienation. Parental alienation describes actions that a parent takes to intentionally, or unintentionally, distance a child (or children) from the other parent (Darnell, 1998). Results revealed that 13.4% of parents (or 9.03% of the entire sample) have been alienated from one or more of their children. Our findings suggest that tens of millions of adults and their children may be impacted by parental alienation, which is much higher than previous estimates. Furthermore, findings show evidence of parental alienation across all socio-economic and demographic indicators. However, when compared to Census estimates of different demographic groups in the U.S. population, targeted parents were over-represented among Blacks/African Americans and Native Americans, and those with only a high school diploma level education. The sheer magnitude of parental alienation uncovered in this study indicates the need for more attention to be paid to this important and pervasive problem. Highlights: Prevalence of parental alienation was examined among a randomly selected sample of adults in North Carolina, U.S. Prevalence of parental alienation was considerably higher than previous estimates. Over 22 million adults are estimated to be the targets of parental alienation in the U.S. alone. It is estimated that 10 million adults are experiencing what they perceive to be severe alienation from their children.